(untitled) (Nexo Revista Científica, 2021)
In this study, drying kinetics and thermodynamic analysis of tomato were conducted in a tunnel dryer. Drying experiments were performed at three temperatures (100, 115, and 130 °C) and an air velocity of 1.45 m/s. From the drying curves, only a falling rate period was observed. Under these conditions, a characteristic drying curve was determined. It is observed that at the 40 minutes of the drying process, the outlet gas enthalpy achieved a maximum value that is very close to the inlet value and remained constant until the end of the process. Entropy exhibited similar behaviour to enthalpy. The maximum value of the exergy efficiency curve corresponds to the maximum value observed within the drying rate curves. This maximum value represents the stage when the available energy is efficiently used in moisture removal. As the drying rate decreases the available energy is started to be less employed.